Boosting Na-ion diffusion by piezoelectric effect induced by alloying reaction of micro red-phosphorus/BaTiO3/graphene composite anode. (December 2019) - Mi, Hongwei; Wang, Yingtao; Chen, Hao; Sun, Lingna; Ren, Xiangzhong; Li, Yongliang; Zhang, Peixin
Abstract: Red phosphorus (red-P) has been studied intensively due to its high theoretical capacity. However, it remains a challenge to achieve outstanding rate performance because of a large ion radius of Na + and insulation of red-P. Herein, BaTiO3 (BTO) is used as functional additive to promote Na + diffusion based on piezoelectric effect induced by volume expansion of red-P. Micro red-Phosphorus/BaTiO3 /Graphene (red-P/BTO/G) composite is prepared via a ball-milling method. After 100 cycles, the discharge capacity remains 823 mAh·g −1 . The good performance of micro red-P/BTO/G composite is attributed to the enhanced diffusion kinetics brought by BTO, which makes the speed 110 times faster than red-P/G composite. Moreover, an increased diffusion rate has been acquired through polarization of BTO in high voltage electric field to get aligned polarization direction, with the speed 1.8 times of unpolarized red-P/BTO/G material. The mechanism how BTO promotes Na + diffusion in discharge process is explained in detail. Graphical abstract: Image 1 Highlights: Red-P/BTO/G composite shows Na + diffusion speed 110 times faster than red-P/G. The mechanism how BTO promotes Na + diffusion in discharge process is explained. Micro red-P/BTO/G composite delivers high discharge capacity of 823 mAh·g −1 for long cycling.